Synthesis and Confirmatory Factor Analysis of Components of Functional Competencies of Heads of Departments - Teerasak Aebsapap; Boonchan Sisan; Pariyaporn Tungkunanan (International Journal of Instruction, 2022)
This research project has the objective of synthesizing and doing confirmatory factor analysis of components of functional competencies of Heads of Departments of secondary schools under the Office of the Basic Education Commission in Thailand. The technique of the content analysis consists of 3 steps, namely, document synthesis, making inquiries on opinions and carrying out confirmatory factor analysis. The population is the head of the learning group at the secondary school level. The sample group was the head of the learning group at the secondary school level. under the Office of the Basic Education Commission, 500 people. The findings from the research are as follows. There are 7 components, namely, 1) Professionalism Development 2) Curriculum, Measurement and Evaluation of Learning 3) Educational Innovation and Information Technology 4) Intellectual Leadership 5) Quality Management 6) Learning Organization and 7) Professional Ethic. In addition, it is also found out that the development of Heads of Departments needs the clear identification of desirable characteristics in order to develop tools, direction or model that facilitate Heads of Departments to run activities for developing functional competencies of Heads of Departments to cover all dimensions, from personnel recruitment to development and retention. From an overview of secondary schools under the Office of the Basic Education Commission in Thailand, things that are important and necessary for the development of functional competencies of the Heads of Departments of secondary schools in Thailand are the components of the model, which are essential for the planning and development of the quality of Heads of Departments in the sustainable way.
Keywords: Competency Development and Evaluation; Teacher Education and Leadership Studies